Functional seizures across the adult lifespan: female sex, delay to diagnosis and disability. (October 2021) - Kerr, Wesley T.; Sreenivasan, Siddhika S.; Allas, Corinne H.; Janio, Emily A.; Karimi, Amir H.; Dubey, Ishita; D'Ambrosio, Shannon R.; Smith, Jena M.; Engel, Jerome; Feusner, Jamie D.; Stern, John M.
Highlights: 19% of patients with functional seizures (FS) presented after 50 years old. Time from first seizure to video-EEG increased for older patients with FS. Patient younger than 30 had less work disability than older patients. Specific ictal behaviors were similar across the adult lifespan of FS. Abstract: Objective: The clinical characteristics of functional seizures may vary based on age-of-onset or age-of-presentation. Description of age-related differences has focused on three categories: pediatric, young-adult, and older-adult. We evaluated how factors continuously varied based on age-of-presentation across the adult lifespan. Methods: Based on cross-sectional data from 365 adult (18 to 88 years old) patients with documented diagnoses of functional seizures, we evaluated how the quantity and prevalence of specific ictal behaviors, historical factors, and comorbidities varied based on patient age-of-presentation using sequential weighted averages. Results: Four factors changed prominently with age-of-presentation: female predominance decreased at two inflection points - ages 35 and 62; the prevalence of work disability was higher until age-of-presentation 30 then plateaued at 80%; there was greater delay to diagnosis in older patients; and comorbidities was higher with age-of-presentation, starting from early adulthood. The proportion of patients who presented with functional seizures decreased after 50. Ictal behavior did not substantially vary with age-of-presentation. Conclusion: The time from onset to diagnosis increased with age-of-presentation, which may be related to increased comorbidities and the misconception that FS do not start in older age. The female predominance decreased nonlinearly with age. By age 30, most patients' seizures already had substantial association with unemployment. These findings emphasize that patients can develop functional seizures at any age. The rapid development of disability relatively early in life, which then stays at a high prevalence rate, demonstrates the need for prompt referral for definitive diagnosis and treatment.